Analisa Pemilihan Mesin Pendorong Pokok Kri Clurit-641 dalam Melaksanakan Re Engine Untuk Mendukung Operasi di Wilayah Koarmada I - Rio Rakhman Al Mukharom; Budi Sugiarto; Panji Agung Nugroho (JURNAL SYNTAX IMPERATIF : Jurnal Ilmu Sosial dan Pendidikan, 2025)
KRI Clurit-641 is one of the naval defense assets of the Indonesian Navy operating under the jurisdiction of Koarmada I and holds a strategic role in maintaining maritime security stability. However, due to aging components and the high intensity of operational deployment, the vessel has encountered several technical issues, including decreased engine performance, increasing frequency of propulsion system failures, limited availability of spare parts, and rising maintenance costs. These challenges necessitate the implementation of a re engine program to ensure optimal operational readiness. This study aims to identify the main criteria and sub-criteria for selecting a replacement propulsion engine, determine the most suitable engine alternative, and formulate a supporting strategy based on internal and external conditions. The Analytical Hierarchy Process (AHP) method is applied to evaluate the priority of each criterion and determine the best alternative, while SWOT analysis is used to develop an appropriate implementation strategy. The research findings indicate that the Technical Requirement criterion, particularly the reliability sub-criterion, holds the highest weight at 35.4%, while the Operational Requirement criterion with the strategic sub-criterion follows with a weight of 33.2%. Among the three engine alternatives analyzed, the MTU 12V 2000 M93 emerged as the most suitable choice with a total weight of 36.3%. A diversification strategy is recommended, based on the SWOT position that reflects internal weaknesses but significant external opportunities. Therefore, the re-engine of KRI Clurit should be conducted by aligning technical and strategic considerations with defense policy direction to support sustainable and efficient operations